Peningkatan Kesadaran Politik Pada Generasi Muda di Kabupaten Maros - A Lukman Irwan; Abd. Rasyid J; Ilham Jaya (Jurnal Pengabdian Masyarakat Hasanuddin (JPMH), 2021)
This activity has been carried out in Maros Regency in collaboration with the Maros Regency BAWASLU, in the form of discussions, lectures, and assistance related to Guidance on Increasing Political Awareness of the Young Generation in Maros Regency with the material presented, namely: Democracy, Election System in Indonesia, Money Politics, Millennial Generation, Millennial Generation Participation (Young) in General Elections and Political Education for Millennial Generation (Young). The results of the services that have been carried out (1) This service can change the mindset and increase knowledge for the younger generation related to the level of political participation for the Young Generation increasing and reducing the involvement of money politics, (2) Formulating Maros Regency as a pilot area in high political participation for the younger generation, (3) Supporting the implementation of tasks for the General Election Supervisory Body (BAWASLU) of Maros Regency